A Survey of Excavations and Studies on Ostia (2004–2014)*. (9th September 2016) - Pavolini, Carlo
ABSTRACT: The paper is a bibliographical and critical survey of the archaeological research on ancient Ostia and Portus in the decade 2004–2014. The first part deals with some general themes, such as cults, architectural typologies and urban history, decoration: wall-paintings, mosaics and marble, the guilds and their seats, trades, etc. The second part is a survey of individual monuments and buildings which have been the subject of recent excavations and interpretations. The critical problem of late antique Ostia is treated separately, as well as the archaeology of Isola Sacra and Portus, with the Imperial harbours.